2017
DOI: 10.1136/thoraxjnl-2017-210067
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and neuropsychiatric risks of varenicline and bupropion in smokers with chronic obstructive pulmonary disease

Abstract: In smokers with COPD, varenicline and bupropion do not appear to be associated with an increased risk of cardiovascular events, depression or self-harm in comparison with NRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…In a study of 14,350 smokers with COPD, varenicline reduced the risk of heart failure and depression by 44% (hazard ratio [HR], 0.56; 95% CI, 0.34–0.92) and 27% (HR, 0.73; 95% CI, 0.61–0.86), respectively18.…”
Section: Smoking Cessation Treatment For Specific Populationsmentioning
confidence: 99%
“…In a study of 14,350 smokers with COPD, varenicline reduced the risk of heart failure and depression by 44% (hazard ratio [HR], 0.56; 95% CI, 0.34–0.92) and 27% (HR, 0.73; 95% CI, 0.61–0.86), respectively18.…”
Section: Smoking Cessation Treatment For Specific Populationsmentioning
confidence: 99%
“…There have been only four RCTs, involving a collective total of 1,266 subjects, showing that varenicline is effective even at doses lower than those recommended for the general smoking population (RR = 2.08; 95% CI: 1.56-2.78) 33 . A retrospective study of more than 14,000 patients diagnosed with COPD, with or without cardiovascular or psychiatric comorbidities, showed that, in comparison with the use of NRT, the use of bupropion or varenicline did not increase the risk of cardiovascular or neuropsychiatric events within the first six months of treatment 41 …”
Section: Pharmacological Approachmentioning
confidence: 99%
“…During smoking cessation treatment, the use of a nicotine replacement therapy for a sufficient period of time may help to reduce depressive symptoms (16). The efficacy of varenicline, nicotine patches, and bupropion in terms of the rate at which smokers successfully quit smoking (17) and the frequency of adverse psychiatric reactions, such as depression and self-harm (18,19), do not differ to a statistically significant extent. The frequency of smoking cessation interventions must be increased by more frequent clinic visits, longer counseling sessions, or repeating treatment.…”
Section: Smokers With Psychiatric Disordersmentioning
confidence: 99%